2020
DOI: 10.1371/journal.pone.0227892
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular scattering as a predictor of driving performance in older adults with cataracts

Abstract: Cataracts can limit a person's ability to perform vision-dependent tasks safely, affecting the quality of life of older people. This study examines the relationship between visual function and driving, by studying which visual parameters might be important for predicting driving performance in older drivers with and without cataracts, ascertaining whether the objective measurement of intraocular scattering should be considered in assessment procedures for older drivers. This cross-sectional study involved a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 42 publications
6
32
0
Order By: Relevance
“…Moreover, it is worth noting that the effects of straylight during nighttime driving could complicate driving for older drivers with no eye disease, even in low-beam glare conditions [ 20 ]. Our results are consistent with those of previous studies [ 17 , 20 , 28 ] and suggest that intraocular straylight could be a particularly useful visual parameter to measure when assessing the fitness to drive of older drivers, although this conjecture requires further research.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, it is worth noting that the effects of straylight during nighttime driving could complicate driving for older drivers with no eye disease, even in low-beam glare conditions [ 20 ]. Our results are consistent with those of previous studies [ 17 , 20 , 28 ] and suggest that intraocular straylight could be a particularly useful visual parameter to measure when assessing the fitness to drive of older drivers, although this conjecture requires further research.…”
Section: Discussionsupporting
confidence: 92%
“…Older drivers usually reduce their speed to mitigate the perceived risk due to either the environment or their visual, cognitive, or motor decline [ 35 ]. Nevertheless, according to our results, it has been suggested that reducing driving speed is not enough to eliminate any errors in road sign recognition and hazard avoidance [ 14 ], nor does it improve performance in terms of driving measures (e.g., driving outside the lane) in older drivers with eye disease [ 28 ] or when distracted [ 27 ].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations